Development of Dual and Selective Degraders of Cyclin‐Dependent Kinases 4 and 6. Issue 19 (29th March 2019) - Jiang, Baishan; Wang, Eric S.; Donovan, Katherine A.; Liang, Yanke; Fischer, Eric S.; Zhang, Tinghu; Gray, Nathanael S.
Abstract: Cyclin‐dependent kinases 4 and 6 (CDK4/6) are key regulators of the cell cycle, and there are FDA‐approved CDK4/6 inhibitors for treating patients with metastatic breast cancer. However, due to conservation of their ATP‐binding sites, development of selective agents has remained elusive. Here, we report imide‐based degrader molecules capable of degrading both CDK4/6, or selectively degrading either CDK4 or CDK6. We were also able to tune the activity of these molecules against Ikaros (IKZF1) and Aiolos (IKZF3), which are well‐established targets of imide‐based degraders. We found that in mantle cell lymphoma cell lines, combined IKZF1/3 degradation with dual CDK4/6 degradation produced enhanced anti‐proliferative effects compared to CDK4/6 inhibition, CDK4/6 degradation, or IKZF1/3 degradation. In summary, we report here the first compounds capable of inducing selective degradation of CDK4 and CDK6 as tools to pharmacologically dissect their distinct biological functions. Abstract : Target eliminated : Inhibitors of cyclin‐dependent kinases 4 and 6 (CDK4/6) cannot distinguish between the two highly homologous proteins. However, conversion of existing inhibitors into small‐molecule protein degraders resulted in compounds capable of rapidly, potently, and selectively eliminating just CDK4, just CDK6, or both. These novel chemical probes may have utility in elucidating the homologue‐specific functions of CDK4/6.